Eficiência agronômica de um fertilizante fonte de micronutrientes nas culturas da soja e milho - BARBOSA, Juliano Magalhães (2010)
The present work aimed to value the agronomic efficiency of different doses of a fertilizer fount of micronutrients applied through the soil in soy culture and the residual answer in culture rotation with the corn, by the determination of chemical attributes related with the productivity. The study was performed in field s condition in a Distrofic Red Latosoil in the experimental area of the School of Agronomy and Food Engineering, in Goiânia Goiás. The experiment was performed in the harvests 2007/2008 and 2008/2009 in randomized complete blocks design with five treatments and four repetitions. Fertilizer was used as fountain of micronutrients in the form of powder containing 6,8% of manganese (Mn), 3,9% of zinc (Zn), 2,1% of iron (Fe), 1,2% of copper (Cu) and 1,1% of boron (B), in four doses and as reference the testimony: D 0 0 kg ha-1, D 0,5 33,33 kg ha-1, D 1 66,66 kg ha-1, D 2 133,32 kg ha-1 and D 1C - 66,66 kg ha-1 plus 1,4 t ha-1 of calcium oxide. The fount of micronutrient was applied only in the harvest 2007/2008 associated to the soil preparation, in the harvest of 2008/2009 there was no reapplication and the system of planting was direct, without the soil preparation. The geeting of soil and leaf were carried out in the florescence of the cultures. It can be concluded that the cultures appears to be responsive to the fertilizer by considering the productivity of both the soy and the corn and that the fertilizer doses of 128,63 kg ha-1 and 69,08 kg ha-1 showed to have the best efficiency for the productivity of the soy to the corn, respectively.